Mode I stress intensity factor with various crack types (Fracture and Structural Integrity, 2021)
Presence of cracks in mechanical components needs much attention, where the stress field is affected by cracks and the propagation of cracks may be occurred causing the damage. The objective of this paper is to present an investigation of crack type effect on crack severity in a finite plate. Three cases of cracked plate with three different types of cracks are assumed in this work, i.e., single edge crack, center crack and double edge crack. 2D numerical models of cases of cracked plate are established in finite element analysis (FEA), ANSYS software by adopting PLANE 183 element. Values of FEA mode I stress intensity factor SIF and Von-Mises stress at crack apex are determined for cases of cracked plate under tensile stress with different values. To identify the crack severity, the comparison of FEA results for different cracked cases is made. The comparison showed that, single edge cracked plate (SECP) has the maximum values of mode I SIF and Von-Mises stress at crack apex, i.e. the greatest crack severity is considered. Also, values of FEA Von-Mises stress at crack apex for center cracked plate (CCP) are moderate and for double edge cracked plate (DECP) are the minimum. Besides, in case of high crack lengths, it is found that, FEA results of mode I SIF in case of (CCP) are higher than those of in case of (DECP). Consequently, crack severity is considered as moderate in case of (CCP) and the minimum in case of (DECP). Empirical formulas are used to approximately estimate mode I SIF for all the case studies of cracked plate in this study and the results are compared to those of FEA. A good agreement between analytical and FEA results has been showed by this comparison.
Keywords: Stress Intensity Factor (SIF); Cracked Plate; Crack Severity; Von-Mises Stress; Crack Apex